2017
DOI: 10.1016/j.kint.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Medical Condition Self-Management Scale can be applied to patients with chronic kidney disease

Abstract: Chronic Kidney Disease (CKD) is a major burden on patients and the healthcare system. Treatment of CKD requires dedicated involvement from both caretakers and patients. Self-efficacy, also known as perceived competence, contributes to successful maintenance of patient’s CKD self-management behaviors such as medication adherence and dietary regulations. Despite a clear association between self-efficacy and improved CKD outcomes, there remains a lack of validated self-report measures of CKD self-efficacy. To add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Self-management skills were assessed using a valid and reliable tool known as the Perceived Kidney/Dialysis Self-Management Scale (PKDSMS). It had a reported Cronbach’s alpha of 0.760 in the HD population [ 66 ]. Moreover, the scores of PKDSMS were correlated with the self-management behaviours, self-reported health status and serum phosphate in the HD population [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…Self-management skills were assessed using a valid and reliable tool known as the Perceived Kidney/Dialysis Self-Management Scale (PKDSMS). It had a reported Cronbach’s alpha of 0.760 in the HD population [ 66 ]. Moreover, the scores of PKDSMS were correlated with the self-management behaviours, self-reported health status and serum phosphate in the HD population [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…In CKD, regardless of the stage of the disease or whether a person is receiving dialysis, education can improve self‐management behaviours and clinical outcomes (Bonner et al, ; Joboshi & Oka, ; Lee et al, ; Lin et al, ; Lopez‐Vargas, Tong, Howell, & Craig, ; Welch et al, ) yet there are few suitable patient‐reported outcome measures (PROMs) for this population. The Perceived Kidney/Dialysis Self‐management Scale (PKDSMS) has been used to measure perceived competence in self‐management behaviour in those receiving haemodialysis (Wild et al, ). However, this PROM was modified from a previous instrument designed to measure self‐management in patients with specific medical condition such as diabetes and HIV.…”
Section: Introductionmentioning
confidence: 99%
“…The Perceived Kidney/Dialysis Self-management Scale (PKDSMS) has been used to measure perceived competence in self-management behaviour in those receiving haemodialysis (Wild et al, 2017). However, this PROM was modified from a previous instrument designed to measure self-management in patients with specific medical condition such as diabetes and HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Kimmel et al showed that perception of burden of illness and poor social support correlate with treatment of nonadherence, frequent hospitalization, and mortality . Low self‐efficacy (the ability of an individual to set goals and the belief that those goals can be achieved) is common in dialysis patients and up to a third of patients on hemodialysis have low self‐efficacy …”
Section: Current Gaps In Care Around Clinical and Psychosocial Risk Fmentioning
confidence: 99%
“…105,106 Low self-efficacy (the ability of an individual to set goals and the belief that those goals can be achieved) is common in dialysis patients and up to a third of patients on hemodialysis have low self-efficacy. [107][108][109][110][111][112][113] Self-efficacy is a mediator of self-management behaviors. 108,[114][115][116] A poor sense of the chronicity of ESRD and the adverse effects of nonadherence are common in those with low self-efficacy, and they are more likely to shorten or skip dialysis treatments, have high IDWG, and get hospitalized frequently.…”
Section: Psychosocialmentioning
confidence: 99%